Dynamic Modelling and Modal Analysis of an Offshore Wind Turbine - S. L. N. Vishal; Chandrasekhara C. V. (Journal of Mines, Metals and Fuels, 2023)
Floating wind turbine is one of the promising technology due to its consistent and powerful wind sources in deep-sea zone resulting in high power generation. In the present study a 5 MW baseline spar-type offshore wind turbine is considered for modelling and modal analysis. Sub-systems viz., rotor, nacelle, supporting tower, platform and mooring lines are developed using Ashes software. Commercial software which is specially dedicated for the analysis on onshore and offshore wind turbine. Structural steel is considered for the material properties of the sub-systems. Considering the wind speed and wave effects on the live conditions, modal analysis is carried out. The natural frequencies up to six modes and respective mode shapes are established and reported.